Technological Pedagogy And Content Knowledge: Digitizing 21st Century Learning - Nurlailli Hidayati (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to determine the application of technological pedagogical and content knowledge (TPACK) by teachers in the implementation of Akidah Akhlak subject learning in class XI of Madrasah Aliyah. The research method used is descriptive-qualitative. Data collection in the study was carried out using observation, interview, and documentation techniques. Data validity was carried out using source triangulation and method triangulation techniques. The results showed that the application of TPACK in learning involves the use of technological devices, both non-digital and digital, such as laptops and LCDs, and that teachers are able to use PowerPoint, YouTube videos, and Google Classroom in creating learning materials. Teachers use technology in the classroom to manage learning practices and assess the learning process effectively and efficiently.